2020
DOI: 10.1016/j.ejpb.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Hot EVs – How temperature affects extracellular vesicles

Abstract: In recent years, extracellular vesicles (EVs) and outer membrane vesicles (OMVs) have become an extensive and diverse field of research. They hold potential as diagnostic markers, therapeutics and for fundamental biological understanding. Despite ongoing studies, numerous information regarding function, content and stability of EVs remains unclear. If EVs and OMVs ought to be used as therapeutics and in clinical environments, their stability is one of the most important factors to be considered. Especially for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…We found that the dose-dependent antibacterial activity of Cbv34 OMVs was conserved during 28 days of storage. This result matches recent findings that show extracellular vesicles' inherent stability under different storage conditions [49,50].…”
Section: Discussionsupporting
confidence: 92%
“…We found that the dose-dependent antibacterial activity of Cbv34 OMVs was conserved during 28 days of storage. This result matches recent findings that show extracellular vesicles' inherent stability under different storage conditions [49,50].…”
Section: Discussionsupporting
confidence: 92%
“…CD73, whose beneficial action in graft‐versus‐host‐disease [ 12 ] and cartilage repair [ 13 ] was previously emphasized, was found to play a fundamental role in the exosome‐mediated acceleration of the scratch wound closure of keratinocytes. The loss of activity that was observed upon heating the HS‐5 exosomes at 65 °C also suggests that thermal treatment at higher temperatures, which was previously shown to not substantially affect the morphology or uptake behavior of the vesicles, [ 54 ] should be carefully examined as it may be detrimental to the exosome functionality. Notably, the HaCaT cell model used in this work is frequently used to study skin biology for it retains a normal differentiation capacity, though differing in several aspects from primary human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the sterility of the drug product is critical. EVs were recently shown to maintain stability under autoclave temperatures [88]. More importantly, EV-based drug products were reported to be eligible for sterile filtration using filters with 200 nm pore sizes [87].…”
Section: Production Feasibility and Compliance Of Extracellular Vesicmentioning
confidence: 99%